DC electrical resistivity constraints on hydrostratigraphy in the lower South Platte River alluvial aquifer in northeastern Colorado - Lonsert, Reece, author; Harry, Dennis, advisor; Stednick, John, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2013)
This study uses DC Electrical Resistivity Tomography (ERT) to delineate hydrostratigraphic units within the lower South Platte River alluvial aquifer. The geophysical investigation was conducted at Tamarack Ranch State Wildlife Area in northeastern Colorado, where the South Platte River is artificially recharged via pumping to surface recharge ponds and groundwater flow through the underlying unconfined alluvial aquifer system. Twenty-seven ERT profiles collected within a 4.2 km2 study area on the south bank of the South Platte River define 3 different electrostratigraphic units. The ERT data was correlated with drilling logs and laboratory resistivity measurements to develop a hydrostratigraphic model and confining bedrock surface map. Results indicate 7-25 m thick eolian sand deposits (50-800 ohm-m) serve as infiltration zones and do not readily store groundwater. These eolian deposits form up to 15 m high sand hills in the southern half of the study area, and underlie recharge ponds that are used as water sources for artificial recharge of the river. The underlying alluvium (20-3890 ohm-m) varies from 10-70 m thick and functions as the primary groundwater storage unit. A 10-20 m thick intermittent conductive zone (25-80 ohm-m) occurs within the upper part of the alluvial layer that underlies the sand hills, and is interpreted to be caused by clay deposits that potentially influence initial groundwater flow paths emanating from the recharge ponds. The alluvium is underlain by highly conductive siltstone and claystone bedrock formations (1-60 ohm-m) that confine the aquifer system. The bedrock surface is complexly eroded (1055-1110 m.a.s.l.) and is characterized by prominent large-scale paleo-topographic lows (at typical scales of 700 m wide, 35-40 m deep and 700 m wide, 20-25 m deep) that occur on the northern bank of an incised paleo-channel. These features are interpreted to represent a paleo-topographic surface formed by groundwater outflow in the form of piping and sapping networks. The rugged bedrock topography establishes a previously unrecognized first order control on groundwater flowpaths within the unconfined alluvial aquifer.